Defining the requirements for the pathogenic interaction between mutant calreticulin and MPL in MPN - Elf, Shannon (Blood, 2018)
Mutations in calreticulin (CALR) are phenotypic drivers in the pathogenesis of myeloproliferative neoplasms. Mechanistic studies have demonstrated that mutant CALR binds to the thrombopoietin receptor MPL, and that the positive electrostatic charge of the mutant CALR C terminus is required for mutant CALR-mediated activation of JAK-STAT signaling. Here we demonstrate that although binding between mutant CALR and MPL is required for mutant CALR to transform hematopoietic cells; binding alone is insufficient for cytokine independent growth. We further show that the threshold of positive charge in the mutant CALR C terminus influences both binding of mutant CALR to MPL and activation of MPL signaling. We find that mutant CALR binds to the extracellular domain of MPL and that 3 tyrosine residues within the intracellular domain of MPL are required to activate signaling. With respect to mutant CALR function, we show that its lectin-dependent function is required for binding to MPL and for cytokine independent growth, whereas its chaperone and polypeptide-binding functionalities are dispensable. Together, our findings provide additional insights into the mechanism of the pathogenic mutant CALR-MPL interaction in myeloproliferative neoplasms.